2014
DOI: 10.1186/s12245-014-0030-7
|View full text |Cite|
|
Sign up to set email alerts
|

Self-referred patients at the Emergency Department: patient characteristics, motivations, and willingness to make a copayment

Abstract: BackgroundIn many countries, including the Netherlands, a substantial number of patients visit the Emergency Department (ED) without a referral by a general practitioner. The goal of this study was to determine the characteristics and motivations of self-referred patients (SRPs) at the ED. The secondary objective was to explore SRPs’ opinion about copayments.MethodsA survey, in seven different languages was performed among SRPs from October 2011 until January 2012 at an academic ED in the Netherlands. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 20 publications
(29 reference statements)
4
26
0
Order By: Relevance
“…[23] Some studies show that co-payment is not an important driver for patient choice. [24,25] Other studies show that co-payment reduces the frequency of care use and that this decrease is greater for the social deprived patient groups. [12,26,27] So, co-payment may lead to more inequity and to unsafe situations for the social deprived patients.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…[23] Some studies show that co-payment is not an important driver for patient choice. [24,25] Other studies show that co-payment reduces the frequency of care use and that this decrease is greater for the social deprived patient groups. [12,26,27] So, co-payment may lead to more inequity and to unsafe situations for the social deprived patients.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The reasons for self-referral found in previous questionnaire studies also can be divided into the 2 main themes our study found. 4,5,[8][9][10][11][12][13] To the best of our knowledge, this is the first qualitative study also including patients in urgent triage categories that focused on motives for self-referral to the ED. This gives a better representation of the perceptions of the entire scope of self-referred patients in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients expect that they will get medical treatment faster at the ED or perceive the ED to be easier accessible. Also, people encounter difficulties in gaining an appointment with a GP or have been advised by others to directly attend to an ED . Self‐referred patients in urgent triage categories visit the ED appropriately more often .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us be clear that health care providers, and not the patients, assign the label "unnecessary" or "inappropriate" (van der Linden et al, 2014). From the patient's perspective, there is just the need for care (de Valk et al, 2014). In their point of view, crowding means bad service stemming from inadequate management.…”
Section: Think Quality Not Crowdingmentioning
confidence: 98%